Comparative Analysis of Self-Medication Practices with Antibiotics Among Non-Medical and Medical College Students in India - Dhingra, Manthan; Kaur, Maninder; Gupta, Vikram Kumar; Sagar, Barinder; Singla, Namit; Singh, Simranpreet; Ghosh, Abhra (National Journal of Community Medicine, 2024)
Background: Self-medication is prevalent globally, making the processes easier but raising potential hazards like antibiotic resistance. College students, influenced by social media, exhibit alarming self-medication behaviours. This cross-sectional study surveyed undergraduate students across medical, nursing, and non-health science institutions to assess the self-medication habits, knowledge and attitude of students. Methods: This descriptive cross-sectional study was conducted across various educational institutions from August 2023 to February 2024, targeting undergraduate students aged 18 and over. Using a pre-validated questionnaire, data on socio-demography, self-medication with antibiotics, and related knowledge were collected via Google Forms. The sample size was doubled to 1175 for better statistical power. Data analysis was performed using standard statistical tools. Results: Analysis of data demonstrated that a substantive proportion of students self-medicate with antibiotics. For medical students, convenience was the biggest issue and for non-medical students, it was cost-saving coupled with distrust in doctors. The most common complaint received for self-medication was throat pain. Medical students used textbooks for necessary information whereas non-medical students went to local shops for advice. Patterns differed somewhat in comparison with international studies, indicating regional differences. Strikingly, medical students predominantly relied on academic knowledge and previous experiences while using antibiotics, whereas non-medical students often obtained antibiotics from shops or the internet, making them vulnerable to misdiagnosis and inappropriate treatment. Conclusion: This highlights the importance of implementing specific interventions to reduce unsafe self-medication practices in students.